Diagnostic accuracy of presepsin (sCD14‐ST) and procalcitonin for prediction of bacteraemia and bacterial DNAaemia in patients with suspected sepsis. Issue 8 (August 2016) - Leli, Christian; Ferranti, Marta; Marrano, Umberto; Al Dhahab, Zainab Salim; Bozza, Silvia; Cenci, Elio; Mencacci, Antonella
Abstract : N/A: Early diagnosis and prompt targeted therapy are essential for septic patients' outcome. Procalcitonin (PCT) has been shown to predict bacteraemia and bacterial DNAaemia. Presepsin, the circulating soluble form of CD14 subtype, increases in response to bacterial infections, and is considered a new, emerging, early marker for sepsis. We evaluated the diagnostic accuracy of presepsin in predicting bacteraemia and bacterial DNAaemia in 92 patients with suspected sepsis, and we compared it with that of PCT and C‐reactive protein (CRP). Presepsin median values were significantly higher in bacteraemic vs non‐bacteraemic patients [1290 pg ml −1, interquartile range (IQR) 1005‐2041 vs 659 pg ml −1, IQR 381‐979; P <0.001] and in patients with vs patients without bacterial DNAaemia (1297 pg ml −1, IQR 1001‐2046 vs 665 pg ml −1, IQR 381‐940; P <0.001). Receiver operating characteristics analysis showed an area under the curve (AUC) for presepsin of 0.788 [95 % confidence interval (CI): 0.687‐0.889; P <0.001] in predicting bacteraemia and of 0.777 (95 % CI: 0.676‐0.878; P <0.001) in predicting bacterial DNAaemia, lower, but not significantly different, than those of PCT (0.876, P =0.12 and 0.880, P =0.07, respectively). Both biomarkers performed significantly better than CRP, which had an AUC for bacteraemia of 0.602 and for DNAaemia of 0.632 (all P values <0.05). In conclusion, in patients with suspected sepsis, presepsin and PCT showed a good diagnostic accuracy in predicting both bacteraemia and bacterial DNAaemia, superior to CRP.